(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the effects of Zinc supplementation on heat induced gross changes in testes of adult mice with placebo. Study Design: Experimental study Place and Duration of Study: This study was conducted at the Anatomy Department ANMC Islamabad and Anatomy Department Sialkot Medical College, Sialkot in collaboration with (N.I.H) Islamabad from January 2016 to May 2017. Materials and Methods: Fifty-four adult male BALB/c mice were divided into two main groups. Control group of 18 mice and Experimental group of 36 mice. Control group was further divided into Normal control group of 9 mice and Experimental control group of 9 mice. Normal control group was given neither heat nor given any drug or placebo and were sacrificed on day 0 of the experiment. Experimental control group was given limited body heat and then sacrificed after 48 hours of heat exposure. Experimental group was further divided into two groups, Group C and Group D. Group C was further subdivided into C1, C2, C3.C1 was given limited body heat then placebo (Normal Saline) for 15 days, C2 for 30 days and C3 for 60 days. Group D was further subdivided into subgroups D1, D2, and D3. D1 was given limited body heat then ZnSO4 for 15 days, D2 for 30 days and D3 for 60 days. 6 mice from group C were sacrificed on 15, 30 and 60 days each. 6 mice from group D were sacrificed on 15, 30 and 60 days each. Testes were dissected out for gross examination. Results: Consistency was firm after heat exposure, weight was reduced but it regained after drug treatment. Conclusion: Zinc supplementation completely reverses the gross changes produced by limited heat in testes of adult mice.